(NsTATISTI^ESKIJ ANALIZ SLU^AJNYH POTOKOW W FIZI^ESKOM \KSPERIMENTE (B/s - (NaPANASOWI^(B, (NwLADIMIR wLADIMIROWI^s; (NkOLQDA(B, (NaNDREJ aLEKSEEWI^s; (N~ERNQWSKIJ(B, (NaLEKSANDR fEDOROWI^s ((NmINSK (B:s (NuNIWERSITETSKOE(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 243-254 (207 (NNAZW(B.)s
Keywords: (NfIZI^ESKIJ \KSPERIMENTs -- (NsTATISTI^ESKIJ ANALIZs